Newborn Care Practices among Mother-Infant Dyads in Urban Uganda - Violet Okaba Kayom; Abel Kakuru; Sarah Kiguli (International Journal of Pediatrics)
Background. Most information on newborn care practices in Uganda is from rural communities which may not be generalized to urban settings. Methods. A community based cross-sectional descriptive study was conducted in the capital city of Uganda from February to May 2012. Quantitative and qualitative data on the newborn care practices of eligible mothers were collected. Results. Over 99% of the mothers attended antenatal care at least once and the majority delivered in a health facility. Over 50% of the mothers applied various substances to the cord of their babies to quicken the healing. Although most of the mothers did not bathe their babies within the first 24 hours of birth, the majority had no knowledge of skin to skin care as a thermoprotective method. The practice of bathing babies in herbal medicine was common (65%). Most of the mothers breastfed exclusively (93.2%) but only 60.7% initiated breastfeeding within the first hour of life, while a significant number (29%) used prelacteal feeds. Conclusion. The inadequate newborn care practices in this urban community point to the need to intensify the promotion of universal coverage of the newborn care practices irrespective of rural or urban communities and irrespective of health care seeking indicators.